The Microfinance Institution in Cameroon: Historical Perspectives - Bin, Anyekezeh Kum-Ngong (Advances in Social Sciences Research Journal, 2024)
Using the sociological approach to critical analysis, my paper examines the evolution of the microfinance institution in Cameroon from a historical perspective. It argues that due to a number of significant changes on the national and international scene, the institution has undergone a number of palpable changes to become what it is obvious today. I aim at showing how these varied changes on the socioeconomic landscape have been informing templates of the banking sector and, by extension, the microfinance sector in the country today.